Fundusze aktywów niepublicznych - regulowana forma funduszy private equity/venture capital - Krawiec, Wojciech (Private equity funds - regulated form of private equity/venture capital, 2007)
The aim of this article is to present the private equity funds (colloquially called non-public assets funds) construction as a first Polish regulated form of venture capital e.g. Polish legislation in force. The subjects are non-public assets funds functioning based on art. 196-199 of the Act of Investment Funds dated May 27th 2004. In this article the author describes the evaluation of Polish national acts referring to private equity funds, characterizes the investment policies of these entities and also presents existing private equity funds - based on the Act of Investment Funds.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1186, s. 133-144